Rodent outbreaks : (Rice Res. Inst, 2010)
This book is timely because, in recent years, population outbreaks of rodents in the rice-cropping systems of Asia have escalated. There has been precious little formal documentation of the factors that lead to rodent population outbreaks, their veloping countries.